Shelf-Life Measurement of Dried Fish (Keumamah) using The Accelerated Shelf-Life Testing (ASLT) with The Arrhenius Model using Microwave - Ismail Sulaiman; Ikhsanul Khairi (Universitas Darussalam Gontor, 2024)
Indonesia is one of the archipelagic countries with unlimited potential for fish resources, this is evidenced by the extent of Indonesia's marine waters reaching 295,370 km, stretching from the Indian Ocean to the Atlantic Ocean. The large amount of fish, especially in certain periods, makes the price of fish cheap. Therefore, the fish needs to be processed to produce a more diverse product diversification: wood fish, a typical Acehnese food known as keumamah fish. This keumamah fish can be processed by drying and has a long shelf life, but if improper handling in processing and storage causes this product to spoil quickly. This study looked at pretreatment storage methods so that keumamah fish can be stored longer as measured by the Accelerate Self-Life Testing Method with the Arrhenius model. This study was conducted by drying the fish with preliminary treatment using 50 hertz microwave wave (5 and 7 minutes) and storing the fish packaged using polyethylene plastic in an oven with temperatures of 35, 45 and 55 Celsius and analyzing the critical point on moisture content and microbial count during the storage process. The analysis results show that the shelf life of wood fish with 7 minutes of microwave pretreatment and oven drying at 55 Celsius, the fish can be stored in the oven until 120 days.